TOLERANSI DALAM SURAT AL-MUMTAHANAH PERSPEKTIF TAFSIR AL-MUNIR - Rizky Pratama Putra; Uswatun Khasanah (Wahana Islamika Jurnal Studi Keislaman, 2023)
The purpose of this study is to find out in depth about the concept of tolerance contained the in it, the research of tolerance was raised in surat al-Mumtahanah perspective of Tafsir al-Munir. This type of research is library research with qualitative analysis techniques of thematic approach to letters. The primary data source in this study is taken from the Qur'an and its translation and the book Tafsîr al-Munîr fî al-'Aqîdah wa al-Syarî'ah wa al-Manhaj while the secondary data sources are Quraish Shihab's Tafsir al- Misbah, Aidh al Qarni's Tafsir Muyassar, as well as books and journals related to the theme. The results of this study are: (1) Allah Subhanahu Wata'alaa does not forbid you to be kind to the disbelievers who are at peace with you, do not fight you because of religion and do not drive you out of your hometowns and homes. (2) The verse informs all religious people, that Islam does not forbid to help and relate well with followers of other religions in any form, as long as it is not related to the issue of aqidah and mahdhah (obligatory worship), such as prayer, fasting, Hajj, and so on.